Genetic Manipulation of the Metabolism of Polyamines in Poplar Cells. The Regulation of Putrescine Catabolism - Bhatnagar, Pratiksha (American Society of Plant Physiologists, 2002)
We investigated the catabolism of putrescine (Put) in a non-transgenic (NT) and a transgenic cell line of poplar (Populus nigra × maximowiczii) expressing a mouse (Mus musculus) ornithine (Orn) decarboxylase (odc) cDNA. The transgenic cells produce 3- to 4-fold higher amounts of Put than the NT cells. The rate of loss of Put from the cells and the initial half-life of cellular Put were determined by feeding the cells with [U-(14)C]Orn and [1,4-(14)C]Put as precursors and following the loss of [(14)C]Put in the cells at various times after transfer to label-free medium. The amount of Put converted into spermidine as well as the loss of Put per gram fresh weight were significantly higher in the transgenic cells than the NT cells. The initial half-life of exogenously supplied [(14)C]Put was not significantly different in the two cell lines. The activity of diamine oxidase, the major enzyme involved in Put catabolism, was comparable in the two cell lines even though the Put content of the transgenic cells was severalfold higher than the NT cells. It is concluded that in poplar cells: (a) exogenously supplied Orn enters the cells and is rapidly converted into Put, (b) the rate of Put catabolism is proportional to the rate of its biosynthesis, and (c) the increased Put degradation occurs without significant changes in the activity of diamine oxidase.